Using vocabulary builder app to improve lexical knowledge for ninth graders - Carrera Rivera, Kevin Javier (2023)
This study describes the use of Vocabulary Builder App as a tool for improving lexical knowledge, a unique and fresh educational opportunity in the field of English language learning. Unlike traditional methods involving the memorization of extensive and monotonous vocabulary lists, vocabulary builder reflects the contribution to the development of lexical skills and analyzes the use of English language learning through the use of this didactic tool, an exciting journey of lexical enrichment, thus redefining the way in which new words are acquired. This study focuses on the literature review of studies that contemplate the use of Vocabulary Builder App in the lexical development of the learner's lexicon. The breakthrough of this application lies in its playful and gamified approach. Students embark on an educational, reflective and entertaining learning journey. Through game elements, the app transforms the learning process into a stimulating and exciting experience. This approach not only challenges users to expand their vocabulary, but also encourages active participation and prolonged engagement. Interaction with the app expands the repertoire of words, and allows users to understand how they are used in real contexts